Respectful-Based Assessment: Sebuah Model Asesmen Bimbingan dan Konseling Bagi Klien Dalam Lingkup Komunitas Sosial - Rudi Haryadi; Eka Sri Handayani; Akhmad Rizkhi Ridhani (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2020)
This study aims to develop a new model of non-test guidance and counseling assessment that is relevant to the assumptions of multicultural and social justice oriented which is manifested in the RESPECTFUL framework for clients in the community (outside school). The research design used was the Richey & Klein level 1 PPE model. The assessment model was designed by researcher I based on the results of the literature study. The Delphi questionnaire was then distributed to 3 experts and 4 community practitioners to test the content of the developed assessment. The results of content validation show that the developed model is included in the very good category and can be used in the field with several modifications, such as the need for: (1) target community specifications; (2) correction of the sentence editor; (3) name change; and (4) explanation of the respondent's requirements. However, the effectiveness of its use in the field needs to be further confirmed through field trials. It is recommended for further researchers to conduct field trials of this assessment model with specific target communities and develop a broader assessment in order to reach specific client communities such as people with disabilities, children, and parent.